Symptomatic non-traumatic muscle hernia in the dorsal forearm. (March 2015) - Lim, Ming-Sheng; McInerney, Niall M.; Kelly, Edward J.
Summary: We report an unusual case of a symptomatic non-traumatic muscle hernia in the dorsal forearm. To our knowledge, this is the first report of muscle hernia involving the extensor carpi ulnaris. The reported treatments for muscle hernia are numerous and increasingly complex. We treated our case with a fasciotomy followed by a fasciorrhaphy. The patient remained asymptomatic at follow-up after 6 months. This case highlights that simple procedures are effective without the associated morbidity of complex reconstructions.